2023
DOI: 10.3847/1538-4357/acac99
|View full text |Cite
|
Sign up to set email alerts
|

A New Physical Picture for Active Galactic Nuclei Lacking Optical Emission Lines

Abstract: In this work, we use ∼500 low-redshift (z ∼ 0.1) X-ray active galactic nuclei (AGNs) observed by XMM-Newton and the Sloan Digital Sky Survey (SDSS) to investigate the prevalence and nature of AGNs that apparently lack optical emission lines (“optically dull AGNs”). Although one quarter of spectra appear absorption-line dominated in visual assessment, line extraction with robust continuum subtraction from the MPA/JHU catalog reveals usable [O iii] measurements in 98% of the sample, allowing us to study [O iii]-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 101 publications
0
11
0
Order By: Relevance
“…The notable exception is NSA 631492, which is the lowest-mass, lowest X-ray luminosity object in the sample. Agostino et al (2023) found that LINER-type galaxies have excess X-ray emission across broad 0.5-10 keV for their SFR compared to normal non-AGN galaxies. They separated their X-ray AGN candidates as those having X-ray luminosities more than 0.6 dex above the X-ray luminosity predicted from their SFR.…”
Section: Origin Of X-ray Emissionmentioning
confidence: 96%
See 3 more Smart Citations
“…The notable exception is NSA 631492, which is the lowest-mass, lowest X-ray luminosity object in the sample. Agostino et al (2023) found that LINER-type galaxies have excess X-ray emission across broad 0.5-10 keV for their SFR compared to normal non-AGN galaxies. They separated their X-ray AGN candidates as those having X-ray luminosities more than 0.6 dex above the X-ray luminosity predicted from their SFR.…”
Section: Origin Of X-ray Emissionmentioning
confidence: 96%
“…Though X-rays are not immune from obscuration effects, X-ray observations have been well utilized to identify and study the properties of active galaxies (i.e., see Brandt & Hasinger 2005 and references therein). Sufficiently bright X-ray emission is often used to confirm the presence of AGN in systems lacking other AGN indicators (e.g., Birchall et al 2020;Agostino et al 2023;Messick et al 2023, submitted). Agostino et al (2023) studied local type 2 AGN selected by X-ray emission that lacked apparent optical emission lines.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the absence of narrow [O III] emission in the hyperluminous quasar J0100+2802 could point toward evolutionary effects in the quasar spectra and might be a sign that the narrow-line region (NLR) around the quasar has already been cleared by strong quasar-driven winds on a relatively short timescale (Vietri et al 2018;Coatman et al 2019). Alternatively, it has been suggested recently that underluminous [O III] emission in quasar spectra might be linked to a low gas content in the NLR of the quasar (Agostino et al 2023). Upcoming additional rest-frame optical spectra of high-redshift quasars observed with JWST will be required to shed more light on the evolution of the NLR at high redshifts.…”
Section: Equivalent Width Of the Quasar's [O Iii] Emissionmentioning
confidence: 99%